2015
DOI: 10.1016/j.amjcard.2015.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Mortality Associated With QT and JT Intervals at Different Levels of QRS Duration (from the Third National Health and Nutrition Examination Survey)

Abstract: QT prolongation in the setting of QRS>120 ms is believed to be triggered by prolonged depolarization rather than repolarization. Hence, JT interval is suggested as an alternative to QT interval when QRS duration is prolonged. It is unclear, however, if JT and QT intervals portend similar risk of mortality for different durations of QRS. We examined the association between QT and JT, separately, with all-cause mortality across different levels of QRS duration in 8,025 participants (60±13 years, 41% white, and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 28 publications
2
23
0
2
Order By: Relevance
“…The assessments were based on measuring the JT rather than the QT intervals, because in the setting of delayed ventricular conduction attributable both to the epicardial pacing and Na + channel blockers effects, a wide QRS complex can significantly contribute to the overall QT duration, thus reducing its specificity in detecting repolarization derangements. Clinically, the risk of incident cardiovascular events is better predicted with measurements of the JT rather than the QT interval [ 57 59 ]. It is also noteworthy that in isolated, perfused hearts, the QT interval typically grossly exceeds ventricular action potential duration, and the QT is less sensitive to changes in pacing rate and drug effects, when compared to the corresponding variations in APD 90 [ 60 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The assessments were based on measuring the JT rather than the QT intervals, because in the setting of delayed ventricular conduction attributable both to the epicardial pacing and Na + channel blockers effects, a wide QRS complex can significantly contribute to the overall QT duration, thus reducing its specificity in detecting repolarization derangements. Clinically, the risk of incident cardiovascular events is better predicted with measurements of the JT rather than the QT interval [ 57 59 ]. It is also noteworthy that in isolated, perfused hearts, the QT interval typically grossly exceeds ventricular action potential duration, and the QT is less sensitive to changes in pacing rate and drug effects, when compared to the corresponding variations in APD 90 [ 60 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study did not include a direct index of malnutrition, which has been suggested as a risk factor for SUNDS. 52,53) However, the data on body mass index and the physician's examinations of the participants suggest that they were all in the normal body mass index range for their age (18.5-25 kg/m 2 ), and none of them displayed any overt signs of malnutrition in their history and physical examinations. Future studies should also monitor serum magnesium (an important contributor to cardiac function), genetic profile, electrocardiography, and direct or indirect measure of autonomic nerve activity.…”
Section: Limitations In the Interpretation Of The Current Studymentioning
confidence: 91%
“…1 The presence of a bundle branch block (BBB) represents a particular challenge in properly measuring the QTc interval. 2 Following international recommendations, QT interval should be measured in leads showing the longest QT interval, which is usually in right precordial leads. 3 In presence of a right bundle branch block (RBBB) or a bifascicular block, these leads are strongest affected by conduction delay and therefore hamper adequate measurement.…”
Section: Introductionmentioning
confidence: 99%